The importance of Error Correction in EFL Contexts: a comprehensive Narrative Review - Amal Ebrahem Hassan Bedalla; Mardiya Abobaker Yousef Elzouki (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2025)
Recently correcting students’ errors has received significant attention from the perspective of both researchers and teachers. It is foundational component of second language instruction, particularly within English as Foreign Language (EFL) contexts. While some scholars advocate for explicit correction to enhance accuracy, others emphasize implicit methods to increase fluency and learner autonomy. This inclusive narrative review explores the role and impact of error correction in English as Foreign Language (EFL) settings. It synthesizes key findings from various previous studies on error correction strategies, their effectiveness, and their impact on EFL learners’ linguistic development. It stresses on some theoretical perspectives on types of error correction methods, including teacher correction, peer, and self-correction as well, and their implications for linguistic accuracy and learner development. Grounded in two theoretical perspectives that inform error correction in EFL contexts. Swain’s Output Hypothesis (1985) and Long’s Interaction Hypothesis (1996). While corrective feedback has long been an important part of language pedagogy, timing, debates persist regarding its optimal application, and psychological impact. This comprehensive narrative review aims to highlight both the benefits and challenges related with error correction and provide evidence-based recommendations for EFL educators. This review emphasizes the importance of adopting more balanced and psychologically considerate when applying error correction’s methods —those that not only correct learners’ errors on language forms but also foster learners’ emotional and cognitive development. Future research should explore diverse contexts and incorporate learners’ viewpoints to ensure methods promote effective, equitable language education.